2015
DOI: 10.1007/s13365-014-0311-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical associations of white matter damage in cART-treated HIV-positive children in South Africa

Abstract: A range of factors contributes to white matter damage in vertically infected HIV-positive children. These may include combination antiretroviral treatment (cART) regimen, sociodemographic factors, nutritional-hematological status, HIV-relevant clinical variables, and cognitive functioning. We explored associations between a number of these factors and diffusion tensor imaging (DTI) measures in 50 cART-treated children aged 6 to 15 years. Fractional anisotropy (FA), mean diffusion (MD), radial diffusion (RD), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 37 publications
1
42
1
Order By: Relevance
“…For example, Montiero de Almeida et al (de Almeida et al 2013) revealed no significant differences in the frequency of mild, moderate, or severe cognitive impairment between HIV-C and HIV-B. This is consistent with multiple studies conducted in South Africa and India that describe significant cognitive impairment in HIV+ adults and children (Hoare et al 2015a; Joska et al 2011; Yepthomi et al 2006; Gupta et al 2007; Ghate et al 2014). More recently, our group compared cognitive performances between HIV-C individuals with and without the Tat C31S polymorphism and reported no significant differences in the cognitive phenotype or severity of cognitive impairment by Tat status (Paul et al 2014).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…For example, Montiero de Almeida et al (de Almeida et al 2013) revealed no significant differences in the frequency of mild, moderate, or severe cognitive impairment between HIV-C and HIV-B. This is consistent with multiple studies conducted in South Africa and India that describe significant cognitive impairment in HIV+ adults and children (Hoare et al 2015a; Joska et al 2011; Yepthomi et al 2006; Gupta et al 2007; Ghate et al 2014). More recently, our group compared cognitive performances between HIV-C individuals with and without the Tat C31S polymorphism and reported no significant differences in the cognitive phenotype or severity of cognitive impairment by Tat status (Paul et al 2014).…”
Section: Introductionsupporting
confidence: 67%
“…The extant literature is replete with evidence of cognitive impairment among children and adults with HIV from regions around the world with high frequency of clade C virus (de Almeida et al 2013; Hoare et al 2015a; Joska et al 2011; Yepthomi et al 2006; Gupta et al 2007; Ghate et al 2014; Paul et al 2014; Hoare et al 2015b). While most of these investigations did not sequence the dicysteine motif of Tat to confirm the presence of cysteine or serine at position 31, the results are consistent with our previous cognitive study in which C31S status was defined (Paul et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lower FA, higher MD and RD in the CC and higher MD in the superior longitudinal fasciculus have been demonstrated in ART-naïve children (8-12 yrs) compared to age-matched controls 13 , while ART failure was associated with decreased FA in the left superior and right posterior corona radiata and decreased AD in the left inferior cerebellar peduncle in 50 children on first line ART (6-15 yrs). 14 Regional and whole brain decreases in FA, and increased MD and RD, compared to controls, have been reported in HIV+ children and adolescents (6-20 years) 15,16 irrespective of treatment status. 15 Regional alterations were related to past disease severity, measured by nadir CD4% and peak viral loads.…”
Section: Introductionmentioning
confidence: 95%
“…In a series of studies of vertically-infected HIV+ children, a research group in South Africa reported a possible association of first-line treatment failure with white matter brain dysfunction in pediatric neuro-HIV [46]. …”
Section: Introductionmentioning
confidence: 99%